2017
DOI: 10.1182/bloodadvances.2017011601
|View full text |Cite
|
Sign up to set email alerts
|

CD86 regulates myeloma cell survival

Abstract: Key Points• CD86 mediates myeloma survival via activity from its cytoplasmic tail and the CD28-CD86 interaction facilitates stromal independence.• Blocking the CD28-CD86 pathway is a promising therapeutic avenue for myeloma, as there are already approved agents that target this pathway.Although prognosis for patients with multiple myeloma has improved over the past decade, research toward discovery of new therapeutic avenues is important and could lead to a cure for this plasma cell malignancy. Here we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 42 publications
(34 reference statements)
1
25
0
Order By: Relevance
“…CD86, which is the cognate ligand for the prototypic T cell co-stimulatory molecule CD28, is expressed by myeloma cells and is required for their survival [148]. Since we have shown that CD28 itself is important in myeloma progression and survival [121,122,149], this CD28/CD86 axis may represent a possible mechanism by which cis-interactions in the myeloma cell microenvironment may facilitate survival and disease progression.…”
Section: Cd28: Bridging the Bmme And Intrinsic Survival Programs In Lmentioning
confidence: 83%
“…CD86, which is the cognate ligand for the prototypic T cell co-stimulatory molecule CD28, is expressed by myeloma cells and is required for their survival [148]. Since we have shown that CD28 itself is important in myeloma progression and survival [121,122,149], this CD28/CD86 axis may represent a possible mechanism by which cis-interactions in the myeloma cell microenvironment may facilitate survival and disease progression.…”
Section: Cd28: Bridging the Bmme And Intrinsic Survival Programs In Lmentioning
confidence: 83%
“…Recent studies have shown that LLPCs primarily use FAO to generate ATP ( Lam et al, 2016 ). To determine if CD28 regulated LLPC metabolism, we first analyzed gene expression in three human CD28 + MM cell lines following CD28 knockdown (KD) ( Gavile et al, 2017 ), as CD28 activation in MM very closely mirrors what is seen in primary PCs ( Boise et al, 2014 ). Several Gene Ontology pathways directly associated with mitochondrial metabolism were significantly downregulated by CD28 KD, including mitochondrial electron transport and the tricarboxylic acid cycle ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…The murine PC line XXO responds to CD28 activation but has heterogeneous CD28 expression, so we began by flow-sorting into CD28 high and CD28 low populations ( Figure 5A ). Both expressed comparable levels of CD80 and CD86 ( Figure S3A ), which allows endogenous CD28 activation ( Gavile et al, 2017 ; Murray et al, 2014 ) and comparison of CD28 high versus CD28 low XXO metabolic profiles without exogenous CD28 activation. We first examined glycolysis by real-time measurement of the extracellular acidification rate (ECAR), an approach that has been established for T cells and LLPCs ( Lam et al, 2016 ; van der Windt et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…This process involves K + channels, putatively explaining the relationship among these two minerals and CD86. The PI3k-akt signalling pathway is activated after CD86 protein binds to the CD86 receptor in an antigen-presenting cell, leading to downregulation of integrins, components of the ECM 34 .…”
Section: Discussionmentioning
confidence: 99%